2014
DOI: 10.4103/0974-8520.146206
|View full text |Cite
|
Sign up to set email alerts
|

An observational pilot study on the effect of Gomutra Haritaki, diet control and exercise in the management of Sthaulya (obesity)

Abstract: Background:India is currently witnessing rising numbers of people in the middle-class who are obese. A lot of the Indian population has started relying on processed foods that contain a huge percentage of trans-fat, sugars, and other unhealthy and artificial ingredients. Obesity is considered the core of many diseases. Increased weight carries significant health risks for some cancers, diabetes, heart diseases and strokes. Junk food, alcohol and sedentary lifestyle are leading us to silent self destruction, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Sthaulya is a disease in which there is abundant growth of Medodhatu in the body beyond normal limits. It is one of the Santarpanottha Vikaras(Disease due to consumption of excessive calories) [14]. Studies on basti were reported by Hiware et al [15] and Bhende et al [16] Studies on Obesity and different assessment tools were reviewed [17][18][19].…”
Section: Sthaulya (Obesity)mentioning
confidence: 99%
“…Sthaulya is a disease in which there is abundant growth of Medodhatu in the body beyond normal limits. It is one of the Santarpanottha Vikaras(Disease due to consumption of excessive calories) [14]. Studies on basti were reported by Hiware et al [15] and Bhende et al [16] Studies on Obesity and different assessment tools were reviewed [17][18][19].…”
Section: Sthaulya (Obesity)mentioning
confidence: 99%